Integration of information and communication technology in the sports field and presentation of some models currently applied - Fatah, A. (Journal of Sports Science Technology and Physical Activities, 2023)
The Object of the study aims to demonstrate the importance of the integration of Information and Communication Technology in sports training and physical education and sports sessions. For this purpose, we used a systematic review method by analysing scientific articles and Congresses and make a selection of handy and less expensive technologies to use in sports training and physical education and sports sessions. After collecting the results and having treated them, we conclude that Information and Communication Technologies or ICT represents an important potential of educational innovations and an almost infinite reservoir of new practices for coaches as for teachers in sports field. The multimedia tools of small size such as tablets, smartphones, digital camcorders, became very practical to inquire on its physical practice and make techniques almost perfected. On this basis, the study recommended to use these technologies that allow athletes and pupils to progress and to reach the objectives of sports training and physical education.